The Effect OF Audit Committee Characteristics ( Committee Size , Committee Independence , Committee Gender Diversity ,Committee Frequency Of Meetings On Jordanian Firm Performance TQ - Jwailes, Ahmad Rajab; Hamada, Rasha (IJRDO - Journal of Business Management, 2021)
This paper seeks to investigate the effect of audit committee characteristics on the company’s performance. The sample consists of 198 non-financial companies listed on the Amman Stock Exchange (ASE) over the period 2010-2020. The results of the study show that the audit committee size, independence and gender diversity have a significant positive relationship with firm’s performance TQ whereas experience and frequency of meetings has an insignificant association. The results of the study could be beneficial for managers and boards in making suitable choices about audit committee characteristics and corporate governance mechanisms to enhance the company’s performance. The study gives policy makers a better understanding of the different characteristics required of an audit committee, for incorporation in future policy preparation to protect the shareholders’ interests. The relationship between audit committee characteristics and company performance is still ambiguous. This study contributes to the literature by identifying the role of audit committee characteristics in company performance, providing evidence for the view that performance is driven by specific audit committee characteristics.